NMR Libraries of Natural and Synthetic Monosaccharides - Pushpraj Singh, (Asian Journal of Pharmaceutical Research and Development, 2026)
Nuclear Magnetic Resonance (NMR) spectroscopy is a cornerstone analytical technique for the structural elucidation of monosaccharides, which are the fundamental building blocks of complex carbohydrates. Due to their structural diversity, including variations in stereochemistry, ring forms (furanose and pyranose), and functional group modifications, accurate identification of monosaccharides remains a significant challenge in glycoscience. To address this, NMR libraries of natural and synthetic monosaccharides have been developed, providing reference spectra for a wide range of sugar molecules under standardized conditions. These libraries typically include both 1D (¹H, ¹³C) and 2D (COSY, HSQC, HMBC, TOCSY) NMR data, enabling comprehensive structural comparisons. Such databases are essential tools for rapid identification, quality control in carbohydrate synthesis, and the interpretation of complex biological mixtures, such as plant extracts or glycoproteins. Synthetic monosaccharides, often labeled or derivatized, are especially useful in expanding NMR libraries to include rare or unstable structures not readily found in nature. Moreover, computational tools and software are now integrated with these spectral databases, improving automated peak assignments and structure prediction. These resources facilitate the study of carbohydrate-related biological processes, such as pathogen recognition, cell signaling, and energy metabolism. The development and continuous updating of NMR libraries not only streamline structural analysis but also contribute to standardization efforts in carbohydrate research. As the demand for glycan-based therapeutics and diagnostics grows, the role of comprehensive NMR libraries becomes increasingly vital in supporting both fundamental research and applied sciences.